The Quantitative states laws in mechanics of fracture - Матченко, Т. І. (Proceedings of National Aviation University (archive), 2003)
The analisis of energetical critcrions was made in mechanics of fracture. The generalized energetical Law of quantitative state of material was offered, which allows to create energetical criterions of quantitative state of material in separate cans